Influenza A Virus Infection Induces Hyperresponsiveness in Human Lung Tissue-Resident and Peripheral Blood NK Cells - Scharenberg, Marlena; Vangeti, Sindhu; Kekäläinen, Eliisa; Bergman, Per; Al-Ameri, Mamdoh; Johansson, Niclas; Sondén, Klara; Falck-Jones, Sara; Färnert, Anna; Ljunggren, Hans-Gustaf; Michaëlsson, Jakob; Smed-Sörensen, Anna; et al. (Frontiers in Immunology, 2019)
NK cells in the human lung respond to influenza A virus- (IAV-) infected target cells. However, the detailed functional capacity of human lung and peripheral blood NK cells remains to be determined in IAV and other respiratory viral infections. Here, we investigated the effects of IAV infection on human lung and peripheral blood NK cells in vitro and ex vivo following clinical infection. IAV infection of lung- and peripheral blood-derived mononuclear cells in vitro induced NK cell hyperresponsiveness to K562 target cells, including increased degranulation and cytokine production particularly in the CD56brightCD16- subset of NK cells. Furthermore, lung CD16- NK cells showed increased IAV-mediated but target cell-independent activation compared to CD16+ lung NK cells or total NK cells in peripheral blood. IAV infection rendered peripheral blood NK cells responsive towards the normally NK cell-resistant lung epithelial cell line A549, indicating that NK cell activation during IAV infection could contribute to killing of surrounding non-infected epithelial cells. In vivo, peripheral blood CD56dimCD16+ and CD56brightCD16- NK cells were primed during acute IAV infection, and a small subset of CD16-CD49a+CXCR3+ NK cells could be identified, with CD49a and CXCR3 potentially promoting homing to and tissue-retention in the lung during acute infection. Together, we show that IAV respiratory viral infections prime otherwise hyporesponsive lung NK cells, indicating that both CD16+ and CD16- NK cells including CD16-CD49a+ tissue-resident NK cells could contribute to host immunity but possibly also tissue damage in clinical IAV infection.